Pengaruh Carbon Emission Disclosure dan Good Corporate Governance terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di Bursa Efek Indonesia Periode 2017-2022 - Fasya, Muhammad; Susilowati, Retno Yuni Nur; Septiyanti, Ratna; Kusumawardani, Niken (Jurnal Studi Pemerintahan dan Akuntabilitas, 2024)
Purpose: This study aims to identify the impact of carbon emission disclosure, independent commissioners, and institutional ownership on firm value. Research methodology: The population used in this study consists of transportation and logistics sector business entities registered on the Indonesia Stock Exchange during the period of 2017-2022, quatitative methods, and SPSS applications. Result: This study concludes that carbon emission disclosure has an effect on firm value. Meanwhile, independent commissioners have no effect on firm value and institutional ownership has an effect on firm value. Limitations: This study identified limitations, specifically in the examination where several business entities were not included in the research sample, resulting in an incomplete sample. Contribution: This study provides empirical evidence that contributes to the literature on the impact of carbon emission disclosures, independent commissioners, and institutional ownership on firm value. Additionally, this study is expected to inform policies related to environmental responsibility in compliance with the Republic of Indonesia Presidential Regulation Number 98 of 2021 on greenhouse gas emission control in national development and OJK Regulation No. 30/SEOJK.04/2016 on corporate obligations to include environmental disclosures in annual reports.